2017
DOI: 10.1111/1467-8268.12298
|View full text |Cite
|
Sign up to set email alerts
|

FDI Determinants in Least Recipient Regions: The Case of Sub‐Saharan Africa and MENA

Abstract: This paper explores the determinants of foreign direct investment (FDI) into FDI least recipient regions. Panel data for 20 sub-Saharan Africa (SSA) and 11 Middle East and North Africa (MENA) countries are used for the period 2000-12.Findings of the fixed effects estimations suggest that FDI inflows into these regions are influenced by GDP per capita, infrastructure development, trade openness, and control of corruption. Conversely, inflation negatively affects FDI inflows, and rents from natural resources do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…The main results showed that the gross domestic production (GDP) per capita was highly important to enhance FDI. This means that higher production would attract more investing in GCC (similar to Okafor et al, 2017). On the other side, inflation affected the FDI significantly and negatively.…”
Section: Literature Reviewmentioning
confidence: 92%
See 1 more Smart Citation
“…The main results showed that the gross domestic production (GDP) per capita was highly important to enhance FDI. This means that higher production would attract more investing in GCC (similar to Okafor et al, 2017). On the other side, inflation affected the FDI significantly and negatively.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Comprehensive studies claimed that the relationship between FDI and GDP per capita is significant and positive (e.g. Cleeve et al, 2015;Okafor et al, 2017). Few studies proved the opposite result (see Dutt et al, 2017).…”
Section: Hypotheses Formulationmentioning
confidence: 99%
“…Corruption is at the forefront of political and economic debates and policies have been defined to reduce it in ECOWAS. As in Okafor et al () and Bonuedi et al (), corruption in this paper is approximated by the index of control of corruption. It reflects the perceptions of the extent to which public power is exercised for private purposes, including small and large forms of corruption, as well as the ‘capture’ of the state by elites and private interests.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Availability of human capital in the form of skilled workers regarded as a great advantage to the firms in their investment adventures in developing countries (Kinda, 2013). An educated workforce has been assumed as an important factor especially for the firms seeking efficiency motive of FDI (Okafor, Piesse, & Webster, 2017). Theory of economics purports that human capital in the shape of education is one of the potent determinants for the influx of FDI (Dunning, 1977).…”
Section: Efficiency-seeking Fdimentioning
confidence: 99%
“…Theory of economics purports that human capital in the shape of education is one of the potent determinants for the influx of FDI (Dunning, 1977). Most of the studies considered various types of measures as proxies for human capital, of which school enrolment ratios and literacy rate are consistently used (Asiedu, 2002;Azemar & Desbordes, 2009;World Bank, 2018a;Kinda, 2013;Kumari & Sharma, 2017;Okafor et al, 2017). The significance of efficiency entails the following hypotheses:…”
Section: Efficiency-seeking Fdimentioning
confidence: 99%